Kajian Hukum Hak Cipta Terkait dengan Penggunaan Sketsa Tugu Selamat Datang oleh Mall Grand Indonesia Berdasarkan (Studi Kasus: Putusan Mahkamah Agung Nomor 35/Pdt.Sus-Hak Cipta/2020) - Apriono, Alwido; Saly, Jeane Neltje (UNES Law Review, 2023)
Decision Number 35/Pdt.Sus-Copyright/2020/PN Niaga Jkt.Pst is a lawsuit for compensation due to the use and registration of the Grand Indonesia Mall Logo mark in the form of a silhouette such as a welcome monument sketch/sculpture. The purpose of the research is to find out the copyright protection of sketches and statues of welcome monuments based on Law Number 28 of 2014 concerning Copyright, and to find out Decision Number 35/Pdt.Sus-Copyright/2020/PN Niaga Jkt.Pst is in accordance with the laws and regulations. The research method used is normative legal research which is descriptive analysis and by writing a literature study. Based on the results of the research, it is known that Decision Number 35/Pdt.Sus-Copyright/2020/PN Niaga Jkt.Pst is inconsistent with the provisions of existing laws and regulations. Because the sketch of the welcome monument and the statue of the welcome monument were created because of an order from President Soekarno to the late Henk Ngantung (in his capacity as Deputy Governor of Jakarta) and the late Edhi Sunarso. Therefore, the creation was made because of the framework of work / office relationship and the existence of orders that made it made because it was under the leadership of the designer of the creation. Therefore, the sketch of the welcome monument and the statue of the welcome monument should be recognized as fully owned by the country.